PENGEMBANGAN ASSESSMENT BERBASIS PROBLEM SOLVING PADA MATERI POKOK KELARUTAN DAN HASILKALI KELARUTAN (Ksp) - Sartika Sartika; Yudha Irhasyuarna; Leny Leny (Universitas Lambung Mangkurat, 2014)
Abstract. There have been development-based assessment of problem solving in the subject matter solubility and solubility product (Ksp). The purpose of this development is to provide appropriate assessment and produce a product that is able to assess students' conceptual understanding and algorithmic. Assessment that has been developed based on the standard of competence, basic competence and learning objectives. Development model used is the model Kemp. This development is done on 10 students of class XI Science SMAN 5 A Banjarmasin academic year 2012/2013 as a small group of test samples and 30 students of class XI IPA 1 SMAN 4 Banjarmasin academic year 2012/2013 as a limited field test sample. Data collection techniques using achievement test techniques, observation and questionnaires. Expert test results obtained average percentage of 95% are good, the results of a small group of students learning test either category 73.81%, 80.63% limited field test is very good category and the average test score student responses is 43 with a small group category as well as a limited field test is 39.47 with either category. That is, the students gave a positive response. Results show the development of problem solving-based assessment in the subject matter solubility and solubility product (Ksp) fit for use in learning. Assessment of students developed can be used in understanding the level of representation in the teaching of chemical solubility and solubility product (Ksp).Keywords: conceptual understanding, algorithmic understanding, problem solving, solubility andsolubility product (Ksp), the level of chemical representation.